Stepwise regression for kenaf reinforced polypropylene composite - Muhammad, Noryani; Salit, Mohd Sapuan; Mohammad Taha, Mastura; Mohamed Yusoff, Mohd Zuhri; Zainudin, Edi Syams (Centre for Advanced Research on Energy, Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka, 2018)
Stepwise regression is an alternative in statistical modelling. This paper discusses the parameters that influence the performance score (PS) of kenaf reinforced polypropylene composite (KRPC). It was found the tensile strength, Young’s modulus and flexural strength are the parameters that influence the materials performance of KRPC. The model adequacy checking was done by plotted the normality and regression probability standardized residual.